2008
DOI: 10.1186/1472-6947-8-45
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Personal Health Records: Transformative Tools for Consumer-Centric Care

Abstract: Background: Integrated personal health records (PHRs) offer significant potential to stimulate transformational changes in health care delivery and self-care by patients. In 2006, an invitational roundtable sponsored by Kaiser Permanente Institute, the American Medical Informatics Association, and the Agency for Healthcare Research and Quality was held to identify the transformative potential of PHRs, as well as barriers to realizing this potential and a framework for action to move them closer to the health c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
211
1
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 364 publications
(229 citation statements)
references
References 21 publications
5
211
1
3
Order By: Relevance
“…Additional recommendations by the Institute of Medicine (IOM) proposed PHR access to a provider's system for data exchange and PHR-facilitated communication between physician and individuals [20]. Additionally, the AMIA, Kaiser Permanente Institute for Health Policy, the Robert Wood Johnson Foundation, and HHS' AHRQ proposed features for facilitating gathering of data from different health care sources [21] (i.e. claims data, commercial laboratories, monitoring devices, etc) and for providing ongoing and secure EMAIL communication between physician and individual, online appointment scheduling, collaborative health tracking and chronic disease management [17], prescription refills, medication reminders, and to report problems.…”
Section: Phr Standardsmentioning
confidence: 99%
“…Additional recommendations by the Institute of Medicine (IOM) proposed PHR access to a provider's system for data exchange and PHR-facilitated communication between physician and individuals [20]. Additionally, the AMIA, Kaiser Permanente Institute for Health Policy, the Robert Wood Johnson Foundation, and HHS' AHRQ proposed features for facilitating gathering of data from different health care sources [21] (i.e. claims data, commercial laboratories, monitoring devices, etc) and for providing ongoing and secure EMAIL communication between physician and individual, online appointment scheduling, collaborative health tracking and chronic disease management [17], prescription refills, medication reminders, and to report problems.…”
Section: Phr Standardsmentioning
confidence: 99%
“…While computerized medical technologies offer the potential to improve workflow and productivity, there is a theoretical point in which increasing productivity becomes offset by potential quality deficiencies. At the same time, healthcare consumers are placing increasing demands on providers for access to healthcare data, collaborative decision making, and quality accountability measures [7][8][9]. The collective stressors of worsening healthcare economics, increased workload, and heightened quality concerns serve as inevitable source of fatigue and stress on healthcare providers.…”
Section: Introductionmentioning
confidence: 99%
“…[21,27,28] Additional EPHR concerns were highlighted that were linked to the sensitive nature of personal healthcare information, which have been identified in several other studies. [13,23,[42][43][44][45][46][47][48][49][50] One third of family members in the current study reported concerns associated with confidentiality and security when considering the implementation of an EPHR. For example, concerns about security of personal information were found at the top of a list of concerns linked with an EPHR in a study conducted by the Markle Foundation (2006).…”
Section: Discussionmentioning
confidence: 99%